Ag nanoparticles immobilized over highly porous crystalline organosilica for epoxidation of styrene using CO2 as oxidant. (January 2022) - Chatterjee, Sauvik; Das, Surajit; Bhanja, Piyali; E. S., Erakulan; Thapa, Ranjit; Ruidas, Santu; Chongdar, Sayantan; Ray, Suman; Bhaumik, Asim
Graphical abstract: We report a new crystalline porous organosilica material, which stabilized tiny AgNPs to obtain a robust nanocatalyst Ag@TSOS-1 that efficiently catalyses the complete conversion of styrene into predominantly styrene oxide using CO2 as an oxidant in a high pressure autoclave reactor. Highlights: A new crystalline porous organosilica material has been synthesized using a tailor made bridging organoslilane precursor. Ag nanoparticles were supported over porous organosilica material to design a novel nanocatalyst Ag@TSOS-1. Ag@TSOS-1 catalyses epoxidation of styrene to styrene oxide using CO2 as soft oxidant. At 20 bar CO2 pressure and 60 °C temperature only styrene oxide and polystyrene formed from styrene. Abstract: Selective epoxidation of olefins is a very important reaction as epoxides are widely been used as platform chemical in polymer and pharmaceutical industries. Unlike conventional oxidants like molecular O2 or peroxides, the use of CO2 as a soft oxidant for the oxidation of olefins is very challenging as it offers the utilization of waste and plentiful CO2 together with the potential for the mitigation of its harmful environmental effect. Thus, this process is cost effective and environmentally challenging. Herein, we report the synthesis of a new crystalline porous organosilica material TSOS-1 with orthorhombic crystal structure by using a tailor made bridging organoslilane precursor prepared through the Schiff base condensation of p -terphenyl-4, 4′'-dialdehyde and 3-aminopropyl-trimethoxysilane. This novel crystalline material TSOS-1 has been synthesized hydrothermally in the absence of any structure-directing agent and it showed high BET surface area (220 m 2 g −1 ) and nanoscale porosity. TSOS-1 is used as a support for stabilizing tiny AgNPs to obtain a robust nanocatalyst Ag@TSOS-1, which efficiently catalyses the conversion of styrene into predominantly styrene oxide (SO) using CO2 as a soft oxidant in an autoclave reactor under mild reaction conditions.